PERTUMBUHAN IMAN KAUM TUNANETRA KEPADA KRISTUS DI MASA PANDEMI COVID-19 DI JAWA BARAT, JAKARTA DAN MEDAN - Tjutjun Setiawan; Andreas Kurniawan; Ronald Rachmat; Linutama Setiyawan; Ferry Simanjuntak (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
During the Covid-19 pandemic, the church was limited by government regulations not to hold on-site service but was replaced with online service via YouTube, Zoom Meetings or other media. Not everyone can use this technology, especially those who have limitations as experienced by the blind. As believers they still have to grow in faith. The problem in the research is how blind people continue to grow in faith in Christ even during the Covid-19 pandemic? This study uses a qualitative method with a literature study approach together with interviews with blind people about the need for their growth in faith. The growth in faith can be obtained through worship, Bible reading. By stopping the weekly service as usual, it is through reading the Bible that they gain faith growth. But they are constrained by funding problems to have a special Bible for them. The result of this research is that the blind need Braille Bible. The author lists the needs of the Braille Bible and distributes it for free as a form of community service. The author hopes that this research can raise the concern of Christians for the needs of the blind and those who need help.